Ultrashort Pulse Reflectometry (USPR) diagnostic for EAST. (1st February 2022) - Domier, C.W.; Zhu, Y.; Pereira, R.J.; Steer-Furderer, J.; Li, X.; Chen, R.; Xu, G.; Sun, P.; Luhmann, N.C.
Abstract: Ultrashort Pulse Reflectometry (USPR) is a plasma diagnostic technique involving the propagation of ultrashort duration (∼few nsec) chirps which contain frequency components spanning large portions of the plasma density profile. Upon reflection, each frequency component reflects from a distinct density layer. The reflected wave packet is down-converted and passed through a multi-channel filter bank, with time-of-flight (TOF) measurements made on each of the filtered wave packets which are then used to reconstruct the electron density profile. Applied previously to the Sustained Spheromak Physics Experiment, UC Davis is updating this technique with higher power (>10X) sources, enhanced channel counts, and high speed customized TOF electronics. A 32 channel USPR system is being developed for the Experimental Advanced Superconducting Tokamak (EAST) device with frequencies spanning 52 to 92 GHz, reflecting from the right-hand plasma cut-off layer. The system will employ three monostatic transmit/receive horns each covering a different waveguide band. Each of the two higher frequency bands will have 8 distinct frequency channels, with the lowest frequency band, spanning 52 to 65 GHz, to have 16 receiver channels to better resolve the EAST scrape-off layer. With a pulse repetition rate of 1 MHz and simultaneous acquisition of all 32 TOF signals, electron density profiles may be obtained with time resolutions of as short as 3–6 µsec.